Effect of shear force on the rotational performance of straight mortise-tenon joints. (July 2022) - Wu, Ya-Jie; Wang, Lei; Lin, He-Shou; Zhang, Li-Peng; Xie, Qi-Fang
Abstract: Straight mortise-tenon joints resist combined shear and bending action, and their rotational performance significantly influences the seismic performance of traditional timber structures in Asian countries. However, current theoretical study on the rotational performance of such joints was based on pure bending action and neglected the influence of shear force. This paper detailed explained the effect of shear force on the load-resisting mechanism of straight mortise-tenon joints. A theoretical analysis method on the moment-rotation relationship of these joints with consideration of shear force was developed and compared to that based on pure bending action. The proposed theoretical method was verified by using experimental results. Parametric study was further conducted, key factor was identified to evaluate the effect of shear force on the rotational performance of joints, and the applicability of theoretical analysis methods with or without consideration of shear force was given. The research indicated that under combined shear and bending, the rotational performance of straight mortise-tenon joints was mainly influenced by the ratio of the net frame span, sn, to the tenon depth dt . With the decreasing of sn / dt, shear force increasingly reduced the rotational stiffness and moment-carrying capacity of the joints. When sn / dt < 10, the influence of shear force should be considered and the moment-rotation curve of the joints should be calculated by using the theoretical analysis method considering shear and bending action. When sn / dt ≥ 10, the influence of shear force can be neglected and the moment-rotation curve of the joints can be calculated only considering bending.